IMMUNOMODULATORY ACTIVITY OF ANTIMICROBIAL PEPTIDE INDOLICIDIN AND ITS STRUCTURAL ANALOGUES - A. Yu. Artamonov (SPb RAACI, 2014)
Immunomodulatory activity of a native antimicrobial peptide indolicidin and its synthetic structural analogues (indolicidin 7, 8,20,21,22), with spatial uncoupling of hydrophobic and hydrophilic parts of the molecule and different net charges was under investigation. It was revealed that indolicidin 7 and 22 at concentrations of, respectively, 0.6 uM and 5 uM suppressed cytotoxic activity of natural killer spleen cells against tumor cells (K-562 line), while indolicidins 8,20 and 21 at the concentrations of 1.3 uM, 2.5 uM and 5 uM respectively, did not influence it. It was shown for the first time, that native indolicidin and its structural analogues indolicidin 8 and 20 did not increase activity of cell division, whereas indolicidin 7 and 22 had a direct mitogenic activity on spleen cells. The investigated peptides showed inhibitory effect upon mitogenic transformation of splenocytes induced by Con A. In addition, indolicidin and its structural analogues suppressed co-mitogenic activity of Interleikin-1 towards splenocytes. The results obtained allow of a conclusion that the structural changes of indolicidin molecule lead to emergence of novel immunomodulatory activities of the peptides, whereas the methods of structural modifications demonstrate potential approaches to directed design of molecules with optimal biological properties.